PENINGKATAN KOMPETENSI GURU SMA MELALUI SOSIALISASI PEMBELAJARAN DEEP LEARNING DI KABUPATEN KUBU RAYA - Yohanes Bahari; Aminuyati Aminuyati; Amrazi Zakso; Jumardi Budiman; Astrini Eka Putri; M. Rikaz Prabowo; Rachmad Agung Prayogi; M. Zainul Hafizi (LPPM Institut Pendidikan Nusantara Global, 2025)
The socialization of deep learning pedagogy represents an essential strategy in responding to the demands of 21st-century educational innovation, particularly for teachers who remain accustomed to conventional methods. This community service program was conducted in Kubu Raya Regency, engaging 50 teachers from various schools and subject areas. The implementation employed lectures, group discussions, question-and-answer sessions, and hands-on practice, structured into three core sessions: understanding the fundamental concepts of deep learning, applying the approach in classroom instruction, and introducing assessment strategies along with a standardized lesson plan template. The results indicated an improvement in teachers’ conceptual understanding, with the majority reporting greater awareness of the characteristics and applications of deep learning. The assessment and lesson plan template sessions were highlighted as the most impactful, as they provided practical tools readily applicable in school settings. The evaluation further revealed teachers’ need for extended practice time, localized case studies, and continuity in the form of advanced training and mentoring. Accordingly, this program can be concluded to have successfully laid the foundation for enhancing teacher competence in Kubu Raya, while also fostering awareness that sustainable follow-up is essential for achieving genuine educational transformation.